Chlorella vulgaris as a Livestock Supplement and Animal Feed: A Comprehensive Review - Ishaya Usman Gadzama; Saraswati Ray; René Méité; Isaac Maina Mugweru; Takudzwa Gondo; Md Atikur Rahman; Md Rahat Ahmad Redoy; Md Fazle Rohani; Ahmed Eid Kholif; Md Salahuddin; Andre F. Brito (Animals)
This review explores the potential of Chlorella vulgaris (CLV) as an alternative supplement in animal feed. CLV is rich in essential nutrients including fatty acids, amino acids, vitamins, and minerals, as well as bioactive compounds such as antioxidants, which contribute to its health-promoting properties. The nutritional composition of CLV can vary depending on factors such as cultivation methods, nutrient availability, light intensity, temperature, water pH, strain, and processing techniques. The rigid cell wall of the microalga limits nutrient accessibility, particularly in monogastric animals. However, processing techniques such as enzymatic treatments can disrupt the cell wall, enhancing nutrient bioavailability and improving its utility as a feed ingredient. Research across livestock species has demonstrated the positive effects of CLV supplementation. For instance, CLV has improved milk production and composition in ruminants, modulated rumen microbiota, enhanced lamb growth, and elevated blood immunoglobulin levels. Moreover, the impact of CLV on ruminal fermentation is dose-dependent, with higher inclusion rates exhibiting more pronounced effects, and it may also play a role in mitigating methane emissions. In poultry, CLV supplementation leads to better growth, feed conversion ratios, immune responses, and meat and egg quality. Similarly, studies on pigs suggest that CLV can benefit immune response and fatty acid profiles, while in rabbits, CLV has been found to reduce oxidative stress and improve immune responses. Additionally, CLV has shown promise in aquaculture, improving feed utilization, immunity, and disease resistance in various fish species. While CLV shows considerable potential, the variability in animal responses and the need for optimized inclusion levels necessitate further species-specific research to elucidate the long-term implications of its inclusion in animal diets.